Evaluation of labor ergonomics of machine milking operators working at milking machines «Carousel» - Yu. A. Tsoy; V. V. Kirsanov; R. A. Mamedova (Аграрная наука Евро-Северо-Востока)
The article shows the assessment of the hourly and shift energy intensity of the operator's work on rotary milking machines with internal milking (of the "Herringbone" type) with the connection of teat cups on the side and on installations with external milking with the connection of teat cups at the back (of the "Parallel" type). The purpose of the study is to determine the indicators of ergonomics and energy intensity of labor productivity of machine milking operators working on rotary milking machines. The conditions that affect the labor productivity of the milking operator are considered. Calculations are presented to determine the indicators of ergonomics and energy intensity of labor of machine milking operators. The data were obtained empirically using the method of chronometric observations of the work of operators in the milking parlor and the principles of a systematic approach. The total mass of loads moved during each hour of the shift from the working surface is exceeded for men (the normal value is not more than 870 kg) and significantly exceeded for women (the normal value is not more than 350 kg) and is 644...1380 kg on Milkline (external) provided that one operator works at the connecting of the milking machine. The total mass of loads is also exceeded for female operators on the AutoRotor 40 (external) and AutoRotor 60 (external) «Carousels» and amounts to 653 kg and 575 kg per operator, respectively. The normal value of the static load per shift when holding the load and applying efforts with one hand for men - not more than 353.0 kN∙s, for women ‒ not more than 215.7 kN∙s. On Milkline installations (external) it is 212.4…455.0 kN∙s when one operator works at the connecting of the milking machine, while the upper limit is significantly exceeded for both men and especially women.